High tolerance of Chaetomorpha sp. to salinity and water temperature enables survival and growth in stagnant waters of central Thailand - Isao Tsutsui; Tatsuo Miyoshi; Dusit Aue-umneoy; Jaruwan Songphatkaew; Chonlada Meeanan; Sirimas Klomkling; Halethichanok Sukchai; Piyarat Pinphoo; Iori Yamaguchi; Monthon Ganmanee; Yukio Maeno; Kaoru Hamano (My University, 2015)
The effects of salinity and water temperature on growth and survival of Chaetomorpha sp., one of the green tidal filamentous algae, were investigated. Field surveys revealed that this alga was abundant throughout the year in stagnant coastal waters of central Thailand. Chaetomorpha sp. was found in salinities of 3.4–90.0 and water temperatures of 20.1–40.9 °C. Chaetomorpha sp. biomass fluctuated between 9.2 and 162 kg dry weight in a saline swamp, without significant differences among seasons. The highest mean specific growth rate of approximately, 60 % day−1 was observed in laboratory experimental trials at salinities of 20–30 at 30 °C. Salinity and water temperature significantly affected growth of this alga independently and interactively. Based on these results, Chaetomorpha sp. can easily grow, survive and monopolize in stagnant waters where the salinity and temperature greatly fluctuate because of their euryhaline and eurythermal nature as well as their high growth rate.
Keywords: Euryhaline; Saline water; Dry weight; Marine and coastal plant biology